2016
DOI: 10.2147/ott.s107913
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction and clinical model building for lymph node metastasis in papillary thyroid microcarcinoma

Abstract: The surgical management of papillary thyroid microcarcinoma (PTMC), especially regarding the necessity of central/lateral lymph node dissection, remains controversial. This study investigated the clinicopathologic factors predictive of lymph node metastasis (LNM) in patients diagnosed with PTMC. Multivariate logistic regression analysis was used for PTMC patients identified from the Surveillance, Epidemiology, and End Results database who were treated by surgery between 2002 and 2012, to determine the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 59 publications
8
19
1
Order By: Relevance
“…This study has also found that the risk of CSD in the male patients was 2.273 times higher than that in the females, similar to the findings by Lin et al 21 . Hsieh et al 22 reported that most elderly male patients in the late stages of the disease were prone to developing lymph node metastasis and distant metastasis, both of which resulted from the levels of sex hormone and unhealthy behavior (such as smoking and drinking).…”
Section: Discussionsupporting
confidence: 91%
“…This study has also found that the risk of CSD in the male patients was 2.273 times higher than that in the females, similar to the findings by Lin et al 21 . Hsieh et al 22 reported that most elderly male patients in the late stages of the disease were prone to developing lymph node metastasis and distant metastasis, both of which resulted from the levels of sex hormone and unhealthy behavior (such as smoking and drinking).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, a sex predisposition was also observed in our study. We found that males were associated with a higher incidence of CLNM, which was also supported by previous reports (16,17,(32)(33)(34)(35). Overall, male patients < 40 years old might be considered a high-risk population for CLNM and should be evaluated carefully when choosing surgical procedures.…”
Section: Discussionsupporting
confidence: 90%
“…Our study suggested that CLNM had a significant tendency to appear in young patients. The optimal cut-off age was 40 years old (AUC=0.648; sensitivity: 0.68; specificity: 0.56), which is similar to previous studies that reported age < 45 years was a risk factor for CLNM (16,17,32,33). In addition, a sex predisposition was also observed in our study.…”
Section: Discussionsupporting
confidence: 89%
“…However, males exhibited a 1.73-fold increased risk of post-thyroidectomy haemorrhage compared to females (OR = 1.73, 95% CI = 1.54-1.94, P < 0.00001), and the reason for the difference is unclear. As male was one of the risk factors of thyroid carcinoma (39), and lymph node metastasis was more likely to happen in male (40), which means that male thyroid surgery may be more complex. Some studies also suggest that male muscles are stronger and their contractions at awakening provoke the slipping of ligatures or the reopening of previously ligated vessels, thus causing haemorrhage.…”
Section: Discussionmentioning
confidence: 99%